2016
DOI: 10.1063/1.4941407
|View full text |Cite
|
Sign up to set email alerts
|

Widely tunable alloy composition and crystal structure in catalyst-free InGaAs nanowire arrays grown by selective area molecular beam epitaxy

Abstract: We delineate the optimized growth parameter space for high-uniformity catalyst-free InGaAs nanowire (NW) arrays on Si over nearly the entire alloy compositional range using selective area molecular beam epitaxy. Under the required high group-V fluxes and V/III ratios, the respective growth windows shift to higher growth temperatures as the Ga-content x(Ga) is tuned from In-rich to Ga-rich InGaAs NWs. Using correlated x-ray diffraction, transmission electron microscopy, and micro-photoluminescence spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…To the best of our knowledge, there are no reports of monolithic nanowire lasers on silicon operating in the telecom-wavelength range. This may be attributed to difficulties in growing high-quality nanowires with proper bandgaps on silicon 11 , as well as non-radiative Auger recombination which increases as the bandgap is decreased 5,12 . Furthermore, the confinement factor and end-facet reflectivity decrease at longer wavelengths in sub-wavelength scale nanowire cavities, implying that the nanowire diameter and length must increase to support longer wavelength lasing 13 .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no reports of monolithic nanowire lasers on silicon operating in the telecom-wavelength range. This may be attributed to difficulties in growing high-quality nanowires with proper bandgaps on silicon 11 , as well as non-radiative Auger recombination which increases as the bandgap is decreased 5,12 . Furthermore, the confinement factor and end-facet reflectivity decrease at longer wavelengths in sub-wavelength scale nanowire cavities, implying that the nanowire diameter and length must increase to support longer wavelength lasing 13 .…”
Section: Introductionmentioning
confidence: 99%
“…[31] Optically pumped laser device based on InGaAs NWs has also been reported, [109] while embedding InGaAs QDs in GaAs NWs has been proven beneficial for near-infrared operating lasers. [110] The growth of InGaAs NWs has been achieved via MOCVD, [31,43,50,[111][112][113][114] CVD [32] and MBE, [20,109,[115][116] either via a catalyst free-approach or by using Au, Ga or In droplets as catalysts. The effect of different parameters on the morphology of the NWs has been examined intensely.…”
Section: 22) Ingaas Nanowiresmentioning
confidence: 99%
“…It has been shown that in order to obtain In-rich, InGaAs NWs the ideal temperature would be 550°C, while the temperature for Ga-rich NWs is 610°C. [115] This is probably attributed to the lower mobility of Ga adatoms, which requires for a higher temperature in order for Ga incorporation in the NWs to be promoted. The above are illustrated in the SEM images of Figs.…”
Section: 22) Ingaas Nanowiresmentioning
confidence: 99%
“…The analysis focuses on InGaAs nanowires grown by catalyst-free molecular beam eptiaxy (MBE) which have been shown to have wide compositional tunability and can be used as a foundation for epitaxial core-shell heterostructures 22,23 for near-IR optoelectronics. We demonstrate reconstruction of single stacking defects and lattice strain in InGaAs nanowires on Si substrates with a spatial resolution better than nm.…”
mentioning
confidence: 99%